Molecular Relationships and Antimicrobial Susceptibilities of Viridans Group Streptococci Isolated from Blood of Neutropenic Cancer Patients - Wisplinghoff, H. (American Society for Microbiology, 1999)
From January 1995 to May 1998, 57 episodes of bacteremia due to viridans group streptococci were identified in 50 febrile neutropenic patients with hematologic malignancies. Four patients experienced two separate episodes of streptococcal bacteremia, and one patient had four separate episodes of streptococcal bacteremia. Strains were identified to species level as Streptococcus mitis (n = 37), Streptococcus oralis (n = 19), and Streptococcus salivarius (n = 1). Epidemiologic relatedness of these strains was studied by using PCR-based fingerprinting with M13 and ERIC-2 primers and pulsed-field gel electrophoresis with restriction enzyme SmaI. All strains that were isolated from different patients exhibited unique fingerprint patterns, thus suggesting that viridans group streptococcal bacteremia usually derives from an endogenous source. Cross-transmission of strains between patients could not be established. Four S. mitis isolates recovered during four separate bacteremic episodes in a single patient had identical fingerprint patterns. Susceptibility testing was carried out by broth microdilution technique according to National Committee for Clinical Laboratory Standards guidelines. The MICs at which 90% of the isolates are inhibited were (in milligrams per liter) as follows: 0.5 (penicillin), 0.5 (amoxicillin), 0.25 (cefotaxime), 2 (chloramphenicol), 4 (erythromycin), 0.5 (clindamycin), ≥32 (tetracycline), ≥32 (trimethoprim-sulfamethoxazole), 4 (ciprofloxacin), 0.5 (sparfloxacin), 0.5 (vancomycin), 0.25 (teicoplanin), and 1 (quinupristin-dalfopristin). High-level penicillin resistance (MIC, ≥4 mg/liter) was found in one isolate only, but intermediate penicillin resistance was noted in 11 isolates (19%). Resistance rates to other drugs were as follows: 7% (amoxicillin), 4% (cefotaxime), 4% (chloramphenicol), 32% (erythromycin), 9% (clindamycin), 39% (tetracycline), 68% (trimethoprim-sulfamethoxazole), 23% (ciprofloxacin), 0% (sparfloxacin), 0% (vancomycin), 0% (teicoplanin), and 0% (quinupristin-dalfopristin).